Density Functional Theory (DFT) and Quasi Harmonic Approximation (QHA) on Isotope effect of Methane Absorbed on Ag(111) Surface - Septia Eka Marsha Putra; Indah Gumala Andirasdini (Department of Physics, Sebelas Maret University, 2024)
We investigated the isotope effect of methane (CH4) on Ag(111) using van der Waals density functional and the quasi-harmonic approximation.In this study, we combined two methods to investigate the nuclear quantum effect in methane adsorption on an Ag(111) surface. We obtained that the adsorption potential energies of CD4on fcc Ag(111) surfaces are shallower than those of CH4, whereas the equilibrium distances from the surface are larger.The similiar finding also observed in our previous study, however, Ag(111) gives smaller energies.It is found that the similar softening of the C-H bond pointing toward the surface is the cause of the isotope effect. This softening leading to lowering the vibrational frequency and large zero-point energy difference between CH4and CD4.